Tensile Strength of Banana Stem and Bamboo Fibres as Alternative Materials in Making Craft Products. - Majid, Ahmad Zuhairi Abdul; Bakhir, Norfarizah Mohd; Yassin, Hafeezur Rahmaan Mohd (2017)
Natural fibres are currently used in various of engineering applications to increase strength and to optimize weight and cost of the product.many types of natural fibres such as coconut husk, straw, pineapple, bamboo and banana are used as reinforcement material.In this paper the banana stem and bamboo fibres were chosen for the development of craft products or as composite materials.